Propriedades físicas de sistemas carbonosos com hibridização mista sp2 - sp3 - Vasconcelos, Fabrício Morais de (2020)
The search for physical and chemical modifications of graphene, in order to tune its electronic properties, stimulated the study of new allotropic forms of carbon with sp, sp 2 or sp 3 hybridizations. Recently, several carbon allotropes showing combinations of different hybridizations have been proposed and investigated. In this study, we propose a new class of quasi-2D carbon nanostructures with mixed sp2 – sp3 hybridization. This class of allotropes contains hexagonal and square rings, exhibiting metallic or semiconductor behaviors depending on the structural parameters that define the structure. The key to manipulate their physical properties is the extension of their graphitic section. As we vary this characteristic, remarkable properties emerge, such as Dirac cones that are allowed by the coupling between the different graphene-like sectors of the system, as mediated by tetra-coordinated carbon atoms. As widely reported in the literature, carbon-based quasi-1D systems can have properties notably different from the corresponding bulk system. Motivated by this fact, we by using theoretical methods investigated the electronic properties of nanoribbons base on these system with mixed hibridizations. We show how the electronic structure of these nanoribbons depend on the chirality, width and details of edge reconstruction. In addition, we predict the existence of different hybridization states at the edges, the modulation of the gap energy and the appearance of spin polarized states, demonstrating a set of versatile electronic behaviors. Our results suggest that these ribbons can be prototypes for future applications in nanoelectronics. We have also investigated, through theoretical calculations, the electronic properties of two classes of corresponding nanotubes. We show that all systems are semiconductors and that gap energy modulation can be obtained by varying the diameter of the nanotubes. Through fundamental properties, we point out aspects that suggest the experimental viability of the studied systems.